An infection control audit in 10 primary health-care facilities in the Western Cape Province of South Africa - Mphahlele, Matsie Theodora; Tudor, Carrie; van der Walt, Martie; Farley, Jason (International Journal of Infection Control, 2012)
In 2009, we conducted a cross-sectional descriptive study to evaluate environmental, administrative and personal infection control measures in ten primary health care facilities in Western Cape Province, South Africa. A standard data collection form was used to collect information on current infection control practices, and through structured interviews of administrative and clinical personnel. Only 2 of 10 facilities had infection control plans specific to their facilities. Adequate supplies of personal protective equipment (respirators) in 8 of 10 facilities; no cohorting of TB patients were done and only half (5/10) of facilities had a designated infection control officer on site.Infection control appears to be inadequate in the facilities studied. TB infection control needs to be strengthened including training and improving infrastructure in primary health care settings in the Western Cape Province.